Implementing identity management on AWS : a real-world guide to solving customer and workforce IAM challenges in your AWS cloud environments - Lehtinen, Jon; Hutchinson, Steve (Packt Publishing, 2021)
Understand the IAM toolsets, capabilities, and paradigms of the AWS platform and learn how to apply practical identity use cases to AWS at the administrative and application level Key Features Learn administrative lifecycle management and authorization Extend workforce identity to AWS for applications deployed to Amazon Web Services (AWS) Understand how to use native AWS IAM capabilities with apps deployed to AWS Book DescriptionAWS identity management offers a powerful yet complex array of native capabilities and connections to existing enterprise identity systems for administrative and application identity use cases. This book breaks down the complexities involved by adopting a use-case-driven approach that helps identity and cloud engineers understand how to use the right mix of native AWS capabilities and external IAM components to achieve the business and security outcomes they want. You will begin by learning about the IAM toolsets and paradigms within AWS. This will allow you to determine how to best leverage them for administrative control, extending workforce identities to the cloud, and using IAM toolsets and paradigms on an app deployed on AWS. Next, the book demonstrates how to extend your on-premise administrative IAM capabilities to the AWS backplane, as well as how to make your workforce identities available for AWS-deployed applications. In the concluding chapters, you’ll learn how to use the native identity services with applications deployed on AWS. By the end of this IAM Amazon Web Services book, you will be able to build enterprise-class solutions for administrative and application identity using AWS IAM tools and external identity systems. What you will learn Understand AWS IAM concepts, terminology, and services Explore AWS IAM, Amazon Cognito, AWS SSO, and AWS Directory Service to solve customer and workforce identity problems Apply the concepts you learn about to solve business, process, and compliance challenges when expanding into AWS Navigate the AWS CLI to unlock the programmatic administration of AWS Explore how AWS IAM, its policy objects, and notational language can be applied to solve security and access management use cases Relate concepts easily to your own environment through IAM patterns and best practices Who this book is for Identity engineers and administrators, cloud administrators, security architects, or anyone who wants to explore and manage IAM solutions in AWS will find this book useful. Basic knowledge of AWS cloud infrastructure and services is required to understand the concepts covered in the book more effectively.